Transition regime effective viscosity of a gas confined in a cylindrical geometry - García Sucre, Máximo; Lameda, Luis; Parra, Rixio; Urbina Villalba, Germán (Ciencia, 1970)
The effective viscosity of a gas in the transition regime confined to a cylindrical geometry is obtained using the path integral method. In the transition regime a pattern of rapid variation of the effective viscosity with the density in equally spaced narrow regions of pressure is found. Those regions are quite unaltered when boundary values are either constant, or variable. For the last case, linear, oscillatory, and random dependences with density have been considered. A discussion is given relating these results to those previously obtained for a planar geometry of two parallel infinite plates.